ОПТИЧЕСКИЕ ИССЛЕДОВАНИЯ КРЕМНИЯ ЛЕГИРОВАННОГО ФОСФИДОМ ГАЛЛИЯ - Зикриллаев, Н.Ф.; Камалов, А.Б.; Турекеев, Х.С. (SCIENCE and SOCIETY, 2022)
In the experiment, KDB-10 single-crystal silicon was used as the starting material. For diffusion, a powder obtained by grinding a gallium phosphide crystal was used as a diffusant. After diffusion, the conduction type was n-type. The appearance of new peaks in their optical properties can be explained by the fact that in silicon the gallium and phosphorus atoms form a binary unit cell.
Keywords: silicon; gallium; phosphorus; diffusion; x-ray